An Analysis of Sexual Assault Support Services for Women who have a Developmental Disability - Martin, Heather M. (Université d'Ottawa / University of Ottawa, 2015)
Guided by feminist social constructionism, intersectionality and the social construction of disability, this thesis investigates the ways that sexual assault support workers and disability support workers in a medium-sized Ontario city construct women survivors of sexual assault who have a developmental disability, and how their service delivery reflects these constructions. The data were collected through semi-structured interviews with sexual assault support workers and disability support workers. Results suggest that these workers construct their service users in multiple, sometimes conflicting, ways, resisting and reproducing several ableist and sexist social constructions. Furthermore, sexual assault support workers and disability support workers often construct their service users in opposing ways. This reveals a divide between the two types of organizations. Bridging this gap may have the potential to improve services for women survivors of sexual assault who have developmental disabilities.
Keywords: Developmental disabilities; Feminist disability studies; Intellectual disabilities; Sexual assault